Analysis of Mathematical Literacy Ability in terms of Learning Independence and Learning with the Sole Model Assisted by E-Module Flipbook Material on Mixed Calculation Operations - Bahrul Ilmi; YL. Sukestiyarno; Endang Wahyuningrum (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to show that mathematics learning using the SOLE (Self Organized Learning Environment) learning model assisted by the Flipbook E-Module achieves quality learning and describes the mathematical literacy thinking process in terms of independent learning in mixed arithmetic operations material. Data collection techniques use unstructured interviews, questionnaires, tests and documentation. This research uses a mixed methods research design with an explanatory design. The data analysis technique uses quantitative analysis followed by qualitative, namely one variable t test, difference test, N-Gain test, and regression test. The results of the research show that: (1) The students' mathematical literacy skills are more than the KKM value, namely 75, with a t-count = 1.975 (> 1.706) and a significance value of 0.042 (< 0.05); (2) There was an increase in mathematical literacy skills by 39.73% after learning with the SOLE model using the flipbook e-module; (3) There is an influence of independence on students' mathematical literacy abilities of 89.6% so it can be concluded that the greater the students' independence, the higher the students' mathematical literacy abilities.